Fertilitas Spermatozoa Ayam Buras dengan Penambahan Antioksidan Glutathione dalam Pengencer Ringer’s Selama Simpan Dingin - iswati iswati; Nurul Isnaini; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
Testing of spermatozoa fertility in vivo is needed to find out the extent of the abilityof spermatozoa fertilization in the female reproductive tract. The fertility ability ofspermatozoa in fertilizing the ovum is indicated by the number of fertile eggs fromthe number of eggs incubated resulting from the mating with Artificial Insemination(AI). The aim of this research is to know the percentage of fertility of eggs from AIusing semen which has been stored cold for 8 hours on Ringe's diluent with theaddition of antioxidant glutathione. Collection semen with teaser female method isdone in Poultry Breeder Installation of Sekolah Tinggi Penyuluhan Pertanian (STPP)Malang. The 30 female chickens were divided into 3 groups of treatment P0: AIusing fresh semen with Ringer's diluent, P1: AI using cold cement with Ringer'sDiluent (8 hours duration storage) and P2: AI using cold semen with 0.5 mMaddition in Diluent Ringe's (8 hours duration storage). Experiment design usingComplete Randomized Design (RAL) and  nonparametric data analysis with chi-square.The observed variable was egg fertility calculated based on egg fertility percentage.The results showed that the dilution treatment had a significant effect (P <0,05) onfertility egg, with the best result indicated by P0 that is 76% fertility, followedby P2 with fertility 42% and P1 which showed the lowest fertility was 34%. IB withcold cement has not demonstrated a good percentage of fertility despite 0.05 mMglutathione added as an antioxidant. It is recommended that AI in domestic poultryusing fresh semen with Ringe's diluent, is done as soon as possible to obtain optimumfertility.